The Potential of Durian (Durio zibethinus) Fruit Peel Extract on Blood Pressure, SOD, and hsCRP Levels in Male Wistar Rats - Hasni Yaturramadhan Harahap; Chandra Pranata (Jurnal FARMASIMED (JFM), 2025)
Hypertension remains a major global health problem and is recognized as a leading risk factor for cardiovascular disease. Its pathogenesis involves complex mechanisms, particularly oxidative stress and chronic inflammation. An imbalance between free radical production and endogenous antioxidant defense, especially the enzyme Superoxide Dismutase (SOD), leads to endothelial dysfunction and elevated blood pressure. In parallel, inflammatory mediators such as interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP) play important roles in the progression of hypertension. Although conventional therapies are effective, they are often associated with side effects and long-term costs, prompting interest in alternative treatments derived from natural resources. Durian peel (Durio zibethinus), usually considered waste, is rich in bioactive compounds such as flavonoids, alkaloids, tannins, and saponins with potential antioxidant and anti-inflammatory effects. This study employed a true experimental design with a post-test control group using male Wistar rats induced with hypertension by L-NAME administration. Animals were randomized into five groups: negative control, positive control (captopril), and three treatment groups with different extract doses. Assessments included blood pressure measurement, SOD activity, IL-6, and hs-CRP levels. Results demonstrated that durian peel extract contained an average flavonoid level of 16.27 mg QE/g with moderate antioxidant activity (IC50 88.90 µg/mL). The highest dose (800 mg/kgBW) reduced blood pressure by 14.2 ± 3.90 mmHg, approaching the effect of captopril (15.03 ± 6.30 mmHg). Moreover, SOD activity increased, IL-6 levels declined at medium to high doses, and hs-CRP levels decreased significantly, nearly comparable to the positive control. In conclusion, durian peel extract shows potential as an antihypertensive agent through mechanisms involving enhanced antioxidant defense and reduced systemic inflammation.